Orthodontic treatment planning for inclusion of the third molar in the dental arches: Part II - Lin John Jin-Jong (Australasian Orthodontic Journal)
Marked lower anterior crowding (late crowding or post-adolescent crowding) often develops at about the time of third molar eruption.1,2,3 Many studies2–12 have implicated the presence of third molars as a cause of this crowding. Despite the fact that there is no clear evidence that this is the case,3–17 many orthodontists and their patients’ referring dentists routinely remove third molars at the retention stage of treatment to prevent crowding later; Ricketts et al.18 even advocate enucleation of the third molar while the patient is very young to prevent future crowding In the following report on two orthodontically-treated patients (the first three cases in this report were published in The Australian Or thodontic Journal, Volume 15, Number 1), the author emphasises the importance of careful consideration of the third molar in the treatment plan.